Single-cell sequencing decodes the secrets of the RAP phenomenon of corticotomy - Fan, Zhibo; Li, Shenghong; You, Liping; Lan, Yuxin; Zhong, Yutong; Ma, Yuefan; Xu, Jie; Xu, Xiaomei (Frontiers in Immunology, 2024)
Corticotomy-assisted tooth movement is commonly performed in clinics, however, its time-limited efficacy and the fear of surgery among patients significantly limit its clinical application. Hence, researchers have investigated non-invasive methods to accelerate tooth movement. However, the molecular mechanisms underlying corticotomy-assisted tooth movement are not fully understood. In this study, single-cell RNA sequencing of digested alveolar bone identified a significant increase in iron metabolism-related genes post-corticotomy. Macrophages play a central role in this field.Following the dimensionality reduction of macrophages, we revealed a new developmental state via pseudotime analysis post-corticotomy. SCENIC analysis revealed that Atf3 is a key transcription factor influencing this new state. We found that Atf3+ macrophages were closely associated with osteoclasts. Moreover, cell chat revealed an increase in cellular communication between Atf3+ macrophages and other cell types after corticotomy. These findings suggested that Atf3+ macrophages might play a key role in corticotomy-accelerated tooth movement, thus providing potential targets for drug development.